Addition of Selenium Nanoparticles to Electrospun Silk Scaffold Improves the Mammalian Cell Activity While Reducing Bacterial Growth - Chung, Stanley; Ercan, Batur; Roy, Amit K.; Webster, Thomas J. (Frontiers in Physiology, 2016)
Silk possesses many beneficial wound healing properties, and electrospun scaffolds are especially applicable for skin applications, due to their smaller interstices and higher surface areas compared to non-electrospun equivalents. However, purified silk promotes microbial growth. In contrast, selenium nanoparticles have excellent antibacterial properties and are a novel antimicrobial chemistry. Here, electrospun silk scaffolds were doped with selenium nanoparticles to impart antibacterial properties to the silk scaffolds. Results showed significantly improved bacterial inhibition and improvement in human dermal fibroblast metabolic activity. These results suggest that the addition of selenium nanoparticles to electrospun silk is a promising approach to improve wound healing with reduced infection, without relying on antibiotics.